Thermal-hydraulic performance of additively manufactured lattices for gas turbine blade trailing edge cooling. (5th July 2022) - Kaur, Inderjot; Aider, Youssef; Nithyanandam, Karthik; Singh, Prashant
Highlights: Thermal-hydraulic performance of four lattice frame materials, namely, Octet, Tetrakaidecahedron, Face diagonal-cube, and Cube is studied for turbine edge cooling application. Face diagonal-cube provided the highest heat transfer coefficient and pressure drop values amongst the investigated samples at similar porosity values and unit cell size. Cube topology yielded the lowest flow losses and consequently highest thermal–hydraulic performance of ∼ 2.78 at the lowest investigated Reynolds number. Abstract: Gas turbine blade trailing edge cooling is challenging because of the stringent geometrical constraints driven by aerodynamics and thermal stresses. The blade topology becomes significantly thin towards the trailing edge which leaves a narrow room for the construction of internal cooling channels and also makes this section susceptible to failure due to thermal stresses. Conventionally, pin-fins are employed in the internal cooling channels of the trailing edge because they provide high levels of heat transfer coefficient values and also structural integrity. Much of the past studies on pin fins have focused on their relative arrangements, heights, crossflow scheme, etc., with an aim to enhance the endwall heat transfer coefficient as well as leverage the conjugate heat dissipation capabilities of these "extended surfaces". Lattices on the other hand, have been investigated to a lesser degree, and some studies can be found for blade mid-chord region, however, with their manufacturability challenges at that time, the concepts did not gain traction. Lattices are far more complex topologies with superior local heat transfer characteristics as well as high conjugate heat dissipation capabilities due to large wetted surface area. With the recent advancements in metal additive manufacturing, complex topologies such as lattices can be revisited due to high chances of their realization now. To this end, we are presenting our study on lattices additively manufactured in 420 Stainless Steel (thermal conductivity nearly twice of Inconel 718), where four different unit cell topologies, (a) Octet, (b) Tetrakaidecahedron, (c) Face diagonal-cube, and (d) Cube, were printed using Binder Jetting technology. The aim of this study is to characterize the conjugate heat transfer capabilities of these lattices manufactured in 420 Stainless Steel prior to conduct similar study with Inconel 718, due to relatively simpler additive manufacturing route of Binder jetting (420 stainless steel) compared to Direct Metal Laser Sintering (Inconel 718). The intended design porosity of the samples was 0.886 and the coupons had single unit cell (edge size of 10 mm) in the thickness. The steady-state experiments were conducted to evaluate the effective thermal conductivity and forced convective heat transfer performance. For forced convection, the experiments were conducted for a wide range of Reynolds numbers with air as the working fluid. Overall heat transfer coefficient, pressure drop, Nusselt number and friction factor enhancement level and pumping power requirements of these structures are presented. The implications of the porosity variation due to manufacturing process on the interpretation of relative performance trends is discussed. The effective thermal conductivity was independent of the topology for considered porosity value. Face diagonal-cube yielded the highest heat transfer and pressure drop for the investigated Reynolds number range. However, Cube provided the best overall thermal hydraulic performance value of 1.94 to 2.78 for the investigated range of Reynolds number. At fixed pumping power conditions, Cube was capable of providing the highest heat transfer coefficient.